Design of a Massage-Inspired Haptic Device for Interpersonal Connection in Long-Distance Communication. (9th July 2018) - Haritaipan, Lalita; Hayashi, Masahiro; Mougenot, Céline
Abstract : The use of tactile senses in mediated communication has generated considerable research interest in past decades. Since massage is a common practice in Asian cultures, we propose to introduce massage-based interactions in mediated communication between people in a close relationship. We designed a device for distant interactive massage to be used during online conversation and we assessed its effect on interpersonal connection with eight pairs of Chinese participants in romantic relationships. All pairs were asked to engage in a conversation, either through a video call or through a massage-assisted video call. The findings showed that the use of the massage device significantly increased the perceived emotional and physical connection between the users. The results also showed a significant increase in the engagement in the massage activity, e.g., total massage time and average force per finger, from positive conversation to negative conversation, demonstrating an evidence of the interplay between audio-visual and haptic communication. Post hoc interviews showed the potential of the massage device for long-distance communication in romantic relationships as well as in parents-children relationships.